Dry Bean: A Protein-Rich Superfood With Carbohydrate Characteristics That Can Close the Dietary Fiber Gap - Brick, Mark A.; Kleintop, Adrienne; Echeverria, Dimas; Kammlade, Sara; Brick, Leslie A.; Osorno, Juan M.; McClean, Phillip; Thompson, Henry J. (Frontiers in Plant Science, 2022)
Consumer food choices are often focused on protein intake, but the chosen sources are frequently either animal-based protein that has high fat content or plant-based protein low in other nutrients. In either case, these protein sources often lack dietary fiber, which is a nutrient of concern in the 2020-2025 Dietary Guide for Americans. Pulse crops, such as dry edible beans (Phaseolus vulgaris L.), are a rich source of dietary protein and contain equal amounts of dietary fiber per 100 kcal edible portion; yet the consumer’s attention has not been directed to this important fact. If product labeling were used to draw attention to the one-to-one ratio of dietary protein to fiber in dry bean and other pulses, measures of carbohydrate quality could also be highlighted. Dietary fiber is categorized into three fractions: soluble (SDF), insoluble (IDF), and oligosaccharides (OLIGO), yet nutrient composition databases as well as food labels usually report only crude fiber. The objectives of this research were to measure the content of SDF, IDF, and OLIGO in a large genetically diverse panel of bean cultivars and improved lines (n = 275), and 2) determine the impact of growing environment on the content of DF. DF was evaluated using the AOAC 2011.25 method on bean seed grown at two locations. Dry bean cultivars/lines differed for all DF components (P ≤ 0.05). IDF constituted the highest portion of total DF (54.0%), followed by SDF (29.1%), and OLIGO (16.8%). Mean total DF and all components did not differ among cultivars/lines grown in two field environments. These results indicate that value could be added by cultivar selection for specific components of dietary fiber.